Social support and self-efficacy during early adolescence: Dual impact of protective and promotive links to mental health and wellbeing. - Megan Cherewick; Rinzi Lama; Roshan P Rai; Choden Dukpa; Dikcha Mukhia; Priscilla Giri; Michael Matergia (PLOS Global Public Health)
This study aimed to assess the impact of sources of social support and dimensions of self-efficacy on psychological symptoms and mental wellbeing among early adolescents. A total of 274 adolescents aged 10-14 from Darjeeling, India, participated in the study. The Multidimensional Scale of Perceived Social Support (MSPSS) and Self-Efficacy Questionnaire for Children (SEQ-C) were utilized to assess dimensions of protective/promotive factors. Nested multivariable regression models assessed associations between age, gender, social support, and self-efficacy on psychological symptoms (internalising, externalising, and total difficulties) and mental wellbeing outcomes (mental wellbeing, optimism, and resilience). Results indicated that 13% of early adolescents screened positive for clinical depression and 44% reported poor mental wellbeing. Emotional and academic self-efficacy, along with family support, were significantly associated with reduced psychological symptoms. Conversely, social, and academic self-efficacy, along with support from friends, were linked to higher levels of mental wellbeing. Regression analyses revealed that dimensions of social support and self-efficacy explained a greater proportion of variability in mental wellbeing outcomes (R2 = 0.37-0.64) than in psychological symptom outcomes (R2 = 0.19-0.22), suggesting a stronger promotive effect on mental wellbeing compared to a protective effect on psychological symptoms during early adolescence. Findings suggest the urgent need for early mental health intervention to strengthen systems of social support and support self-efficacy among early adolescents. Multi-level or sequential interventions that target protective and promotive factors are a key strategy to addressing the global youth mental health crisis.